Remimazolam, a novel drug, for safe and effective endoscopic sedation - Jae Min Lee; Yehyun Park; Dong Won Ahn; Jun Kyu Lee; Kwang Hyuck Lee (Clinical Endoscopy)
Remimazolam is a novel benzodiazepine with unique pharmacokinetic and pharmacodynamic properties, making it an ideal candidate for sedation during endoscopic procedures. Distinguished by its rapid onset and short duration of action, remimazolam offers a safer and more efficient alternative to traditional sedatives, such as midazolam and propofol, with fewer side effects, such as hypotension, bradycardia, and respiratory depression. This article reviews the characteristics of remimazolam and its practical advantages, including ease of use, quick recovery time, and minimal residual sedation, emphasizing its potential to improve patient safety and procedural efficiency in clinical endoscopy settings.